2019
DOI: 10.3390/pharmacy7030105
|View full text |Cite
|
Sign up to set email alerts
|

Deprescribing of Medicines in Care Homes—A Five-Year Evaluation of Primary Care Pharmacist Practices

Abstract: (1) Background: This project evaluates the outcomes of a novel pharmacy-led model of deprescribing unnecessary medications for care home patients. A feasibility study was conducted in 2015 to explore exposure to inappropriate polypharmacy in patients residing in care homes over a one-year timescale. The aim of this study was to present the results of this ongoing service evaluation over a five-year period. (2) Methods: Data collection and risk assessment tools developed during the feasibility study were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This activity reduced the drug burden for the resident and led to the clearer MARs charts reported by care home staff. Previous studies have also reported increased safety of medicine administration when a pharmacist has undertaken medication review [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This activity reduced the drug burden for the resident and led to the clearer MARs charts reported by care home staff. Previous studies have also reported increased safety of medicine administration when a pharmacist has undertaken medication review [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38][39][40][41][42][43] Full-text screening of those 13 records resulted in the exclusion of 8 articles because they did not meet the inclusion criteria. [31][32][33][34][35][36]38,43 The remaining five articles were included in this review. 37,[39][40][41][42] Checking the cited and citing references of the included studies in Web of Science did not lead to any additional studies, nor did the hand search in Drugs & Aging and JAGS.…”
Section: Study Selectionmentioning
confidence: 99%
“…This is a complex and diverse area of practice where knowledge of dementia, pain, and antipsychotic and cardiovascular medication is combined with the assessment and provision of the service and contextualized in relation to effective multidisciplinary working and care home staff training. The clinical reasoning associated with complex case management and medicines review requires knowledge, skills, and experience that are not well codified within pharmacy practice [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further acknowledgement and education involving stakeholders may be helpful for practitioners working in the community and in the care home sector [ 15 , 21 ]. As indicated in the policy development and more recently supported within the Enhancing Health in Care Homes report (NHSE 2020), the presence of a pharmacist as a ‘trusted’ and knowledgeable professional, supports a key quality improvement indicator for care homes.…”
Section: Discussionmentioning
confidence: 99%